An Electrochemical Sensor for Reducing Sugars Based on a Glassy Carbon Electrode Modified with Electropolymerized Molecularly Imprinted Poly-o-phenylenediamine Film - Wang, Qian; Paim, Leonardo Lataro [UNESP]; Zhang, Xiuhua; Wang, Shengfu; Stradiotto, Nelson Ramos [UNESP] (Wiley-Blackwell, 2014)
An electrochemical sensor based on electropolymerizing o-phenylenediamine (o-PD) on a glassy carbon electrode (GCE) was developed for determination of reducing sugars. The molecular imprinted sensor was tested by differential pulse voltammetry (DPV) to verify the changes in peak currents of hexacyanoferrate. Under the optimum analytical conditions, the current change was linear to the logarithm of glucose and fructose concentration from 0.25 to 25 mu M. The detection limit of glucose and fructose were 0.185 mu M and 0.173 mu M, respectively. Besides, the applicability of the sensitive sensor has been successfully evaluated by determining reducing sugars in the samples from sugarcane industries.
Keywords: Reducing sugars; o-Phenylenediamine; Differential pulse voltammetry; Molecularly imprinted polymers